Regulations and treatment strategies for pharmaceutical wastewater - A review - Khan, Afzal Husain (Ecological Questions, 2025)
Pharmaceutical residues are recognized as emerging micropollutants that are predominantly present in the environment, mainly due to direct discharge or inefficiently treated effluents from wastewater treatment plants. Although conventional treatment partially removes pharmaceuticals (less than 50% for most pharmaceutical compounds), it is incapable of completely eliminating pharmaceuticals from wastewater due to the complexity of the compounds and inappropriate operational conditions. However, advanced treatment technology demonstrated a removal rate of over 90%, but cost and energy requirements are considered important aspects. Additionally, a legal and regulatory framework needs to be implemented to control the discharge of pharmaceuticals. Herein, a comprehensive review of global consumption and pathways, as well as guidelines for the efficient removal of pharmaceuticals. Additionally, we examine current developments regarding strict guidelines and policies imposed by various regions aimed at controlling pharmaceutical residues. Finally, we discuss the future outlook for developing new approaches and innovative treatment technologies to reduce pharmaceutical residues in the environment.